iGreen-Risk Management: Integrated Risk Management Model for Sustainable Green Tourism at Sukomakmur Agrotourism Magelang - Idah Kusuma Dewi; Dyan Triana Putra; Ramadhani Purwanto; Ryan Fadhila Firdaus; Nina Mistriani (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to develop an integrated risk management model called iGreen-Risk Management to support sustainable green tourism development at Sukomakmur Agrotourism in Magelang, Indonesia. The research seeks to identify environmental, social, and economic risks faced in green tourism development and create a comprehensive framework that integrates community engagement, participatory decision-making, and critical success factors for sustainable agrotourism management. The study employs Participatory Action Research methodology involving active participation from key stakeholders, including agrotourism managers and local communities. Data collection includes risk identification through stakeholder mapping, focus group discussions, in-depth interviews, field observations, and document analysis conducted over one year. The research follows systematic risk management phases, including risk identification, analysis, evaluation, mitigation, and monitoring. The research is expected to produce a comprehensive iGreen-Risk Management model that provides practical guidelines for agrotourism operators to systematically identify, assess, and manage risks while maintaining environmental sustainability and community welfare. The model integrates environmental conservation, social empowerment, and economic viability principles to ensure long-term agrotourism sustainability. This study contributes novel knowledge by developing the first integrated risk management framework specifically designed for green tourism in agrotourism contexts, combining participatory approaches with comprehensive risk management principles that have not been previously integrated in sustainable tourism literature.